Translation of Pramoedya Ananta Toerâ€™s â€œInemâ€: Enhancement of Local-Global Communication - Dewi, Novita (Universitas Sanata Dharma, 2019)
Translation of a literary work requires the balance between staying faithful to the essence of the original work while creating an artistic, unique, and distinctive piece of work in the translated language so as to evoke the same feelings and responses as the source language. Examining a number of translation strategy used in the translation of Pramoedya Ananta Toerâ€™s short story â€œInemâ€ into English, this study shows that the translation product is to be applauded for two reasons. First, transnational translation of Pramâ€™s work, that is rich in local culture, can connect and define both Indonesian and English cultures better in order to enhance global-local connectedness. Secondly, thanks to the translator, the (recreated) work becomes accessible to readers interested in learning each otherâ€™s language and culture.Keywords: literary translation, local cultures, global-local connectednessÂ